ANALISIS STRUKTUR EKOSISTEM TERUMBU KARANG DI PULAU BUNGIN SEBAGAI BAHAN PENGENALAN EKOSISTEM TERUMBU KARANG BAGI MASYARAKAT - Usman Usman; Subagio Subagio; Akhmad Sukri (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract. The purpose of this research is to know the structure of coral reef ecosystem in Pulau Bungin Kec. Alas Kab. Sumbawa. This research method using Line Transek method by drawing line along 50 meter. From the research, it was found that the coral cover condition that still existed at the research location was 38% in good condition and 62% in damaged condition. Growth of coral reefs found in the study sites such as Acropora Encrusting, Digitate, Non Acropora Foliose, and Massive. Result of analysis of coral reef ecosystem structure for society by using brochure media, introduction of coral reef ecosystem validated by 3 expert which function to give information from result of research to can know that result of brochure is said feasible, can be judged in terms of language feasibility, content and appearance .Validator I in terms of display the achievement level of brochure qualification well with the total score of 75%. Validator II in terms of content level achievement of brochure qualification good with total score of 72%. Validator III in terms of language achievement level brochure qualification well with the total score of 72%. From the feasibility of the language, content, and appearance of brochures the introduction of coral reef ecosystems is feasible for dissemination to the community.